DANCE AND CONTEMPORARILY: METHODOLOGY PERSPECTIVE (Fiep Bulletin - online, 2014)
The present work intended to investigate the possibilities of re-meaning dance as a contemporary corporal practise. For that, a research-action was developed to propose the "problematization", the "theorisation" and the collective reconstruction of the knowledge, to reach possibilities of social intervention. The hermeneutic procedure characterised the phenomenon perspective in the inquiry that was carried through the community people, in its majority university. Lessons of dance with elements/process of the contemporaries' dances and improvisation were carrying out. In this clipping we privilege two significant units, and its sub-units, that had detached of the methodological axle of our intervention: a) the relation with the "other" in the conformation of the dance, in the action and in the appreciation, configuring the observation and the interaction as a way of understanding and appropriation of the dance; b) the relation professor - pupil, who characterised in such a way in the role of who teaches dance, as much as in the role of the methodology of the dance education.
Keywords: dance; contemporarily; method